Estudo sobre o impacto do decreto 28.443/2006 do estado do Ceará na arrecadação de ICMS nas indústrias de confecção - Fonsêca, Fabio Moisés Capistrano da (2017)
In order to broaden the tax base and establish a contributory linearity in the garment industry segment in Ceará, SEFAZ-CE instituted the tax substitution regime for this segment. The objective of the new tax policy was to establish a linear and simplified operational taxation regime; to foster greater competitiveness in the market, to neutralize unfair competition among state taxpayers and to broaden the tax base. In order to verify the impact of this new tax policy on the collection of the sector, the econometric methodology of the Difference in Difference estimator was applied in a database from the years 2004 to 2008 of taxpayers from the state of Ceará and was considered the Decree n ° 28.443 / 2006 as the time frame for a comparison between before and after. In general terms, there was a growth in tax collection for the sector's taxpayers in the MICROEMPRESA collection system, and a reduction in the collection for the taxpayers of the NORMAL and EPP collection system.